Map of Freedom of Religion and Belief and Harmony in Kulonprogo: Social Capital to Face Challenges in the Era of Yogyakarta International Airport (YIA) - Heryansyah, Despan; Arifin, Kamil Alfi (Analisis: Jurnal Studi Keislaman, 2024)
Indonesia is a country with high religious, cultural, and social diversity. Freedom of religion, belief, and harmony between religious communities are important elements to maintain social stability. Normatively, protection for this has been regulated, but its implementation faces challenges, especially in Kulonprogo, which has significant social and religious diversity. This challenge is increasingly complex due to the construction of Yogyakarta International Airport (YIA), which has triggered massive population migration, bringing various religious and cultural identities and increasing the potential for social friction. This study uses a qualitative descriptive approach that is exploratory in nature with primary and secondary data collected through interviews, field observations, and documentation. Data analysis follows the Miles and Huberman model, including data collection, reduction, presentation, and drawing conclusions. The results of the study show that although the construction of YIA brings major challenges, Kulonprogo has strong social capital, such as mutual cooperation, deliberation, and mutual respect, which are the basis for harmony between religious communities. In addition, the presence of religious figures who actively promote tolerance is a key factor in reducing conflict. The principles of justice (‘adl) and reconciliation (islah) in Islam can be an ethical guide for building social harmony through collaboration between government, local communities, and religious figures.